A percepção de idosos sobre seus direitos à saúde - França, Janaína Resende Mendes Marques (2015)
Today the population over sixty years old in Brazil is over twenty millions inhabitants, placing the country in a position among those of the highest number of old people in a world level. With the growth of the old people during the cast decades, the country has been concerned with the creation of programs ande public politics to assure the needs of this population. The objective of this work is to study the perception about the rights of the aged person to health, users of the Family health program. The qualitative method in health has been used, based on the ethnografic method, which has been used with fifteen aged people of both sexes, registered in the basic unity of health, Portal II, Sapé town-PB. The data have been collected through recorded interviews, guided by semisaructured route. Most of the interviewed old people say that theyknow about the rights to health. However, the compreension of the participants of the research about their rights to health is related to the fact that they are weel treated in the hospital, of having medical appointments, of having exams, and receiving medical treatment and receiving medicine promptly. It has been observed that some old people believe that what they receive help or charity of the government prohibit them of knowing about their rights related to health, as well as to life, feeding, leisure time, to freedom, to culture, in short, preventing them of having physical needs, as well as social, economic and political rights. The acquired rights by politicians to old people are not necessarity recognized as such, revealing the fragility of the concept of citizenship in the everyday experiance of the participants as far as the health services are concerned. It´s importante to understand the interface between the public politics of care to old people and their everyday needs.